On the asymptotic properties of analytic on the halfplane functions - Dagienė, E. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Е. Дагене. Асимптотические свойства функции, аналитической в полуплоскости E. Dagienė. Analizinių funkcijų pusplokštumėje asimptotinės savybės